Предмет: Алгебра,
автор: Аноним
Преобразуйте выражение в многочлен стандартного вида
А) (2а-3б)²+(2а-3б)(2а+3б)-аб
Б) 9(9m³+2)-3(3m+1)(1-3m+9m²)
Ответы
Автор ответа:
3
Думаю так
А)(2а+3б)²+(2а-3б)(2а+3б)-аб=4а²+12аб+9б²+4а²-9б²-аб=11аб
Б)9(9m³+2)-3(3m+1)(1-3m+9m²)=81m³+18-3(3m-9m²+27m³+1-3m+9m²)=81m³+18-9m+27m²-81m³-3+9m-27m²=15
А)(2а+3б)²+(2а-3б)(2а+3б)-аб=4а²+12аб+9б²+4а²-9б²-аб=11аб
Б)9(9m³+2)-3(3m+1)(1-3m+9m²)=81m³+18-3(3m-9m²+27m³+1-3m+9m²)=81m³+18-9m+27m²-81m³-3+9m-27m²=15
Похожие вопросы
Предмет: Русский язык,
автор: окно4
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: Mish8989
Предмет: Математика,
автор: kunlove23
Предмет: Биология,
автор: diana3prim